Single-phase seven-level voltage source inverter with low switching frequency - Chaniago, K.; Abd Rahim, N.; Selvaraj, J. (2009)
This paper describes a new configuration of the single-phase seven-level voltage source inverter. The proposed inverter based on modified H-bridge converter. The inverter is built of conventional H-bridge inverter and two bidirectional switches and three bulk capacitor banks. To validate the proposed inverter, a low power prototype inverter has been designed and implemented; analytical, simulation and experiment results have been provided.